THE DETERMINATION OF BUS SERVICE FREQUENCY USING COST-BENEFIT APPROACH - Suwardo, Suwardo (Jurnal Transportasi, 2011)
The determination of bus service frequency using cost-benefit approach is presented in this paper. This study was conducted in Malaysia where bus operators could provide feasible bus services using this method. The investment costs include all costs for vehicle, human resources, workshop, operational facilities, andsupporting facilities while the benefits are expected from ticket fare collected and fuel subsidy. The primary data consists of passenger number, ticket fare, travel time, number of vehicles, and route length. The secondary data, provided by bus operators, include vehicle investment and operation and maintenance costs. The results indicate that this method is applicable and can be used by bus operators to provide feasible bus services with adequate frequencies.Keywords: cost-benefit analysis, bus service, service frequency.